Usage of RDF blank nodes in partial learning - Graorkoski, Velimir; Madevska Bogdanova, Ana (Faculty of Computer Science and Engineering, Ss. Cyril and Methodius University in Skopje, Macedonia, 2012)
The partial learning [1], as an important part of the advanced adaptive learning [1], provides opportunities for developing more efficient adaptive learning [2] process than the one occurring in the basic adaptive learning [1]. This paper explains the representation of the learning environment providing the partial learning, by using the introduction of the blank nodes in the resource description framework [3, 4].